Utilization of palauan (Cyrtosperma merkusii (Hassk) Schott) flour in the production of kroepeck - Celfo, Dinah Elumba
Palauan (Cyrtosperma merkusii (Haskk) Schott.) is one of the indigenous root crops whose commercial value remains low because it is under utilized as food.